Model Pembelajaran Think Pair Share dalam Meningkatkan Kemampuan Berbicara Bahasa Arab di Perguruan Tinggi - Shofiyani, Amrini (Aphorisme: Journal of Arabic Language, Literature, and Education, 2024)
This study aims to examine the effectiveness of the Think Pair Share (TPS) learning model in enhancing students’ Arabic speaking skills in the Arabic language course at Universitas KH. A. Wahab Hasbullah (UNWAHA) Jombang. This research employed a quantitative approach using a quasi-experimental design, specifically the pretest-posttest non-equivalent control group design. The study involved two groups: the experimental group, which was taught using the TPS strategy, and the control group, which received conventional instruction. Data collection techniques included speaking skill tests (pretest and Post-test) and observation of learning activities. Data analysis was conducted using an independent t-test with SPSS version 25. The results revealed a significant improvement in students' speaking skills in the experimental class. The average Post-test score in the experimental group reached 87.1, up from 65.3 in the pretest. Meanwhile, the control group only showed a modest increase from 64.7 to 70.2. The t-test result indicated a significance value of 0.001 < 0.05, suggesting a statistically significant difference between the two groups. Additionally, classroom observations showed that the TPS model effectively increased students’ active participation and confidence in speaking Arabic. Therefore, applying the Think Pair Share model is proven effective and highly recommended as an active learning strategy to improve Arabic speaking skills in higher education contexts.